Transformation of the Bible story in the novel by V. I. Kryzhanovskaya-Rochester “Pharaoh Mernephtah” - Черный, Игорь Витальевич (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article is devoted to the activity of the Russian writer who lived at the turn of the XIXth and XXth centuries V. I. Kryzhanovskaya (Rochester). The novel “Pharaoh Mernephtah” (1888) was examined. Its plot was based on the story of the Old Testament prophet Moses. The author’s peculiarities of pretext interpretation and Moses’ image treatment and the features of his confrontation with the Pharaoh were studied. It was found that the Bible story in the work had undergone the substantial changes. In the first turn that was because of the conservative and monarchist views of the writer, which became a reaction to the social and political situation in Russia at the turn of the XIXth and XXth centuries.